Evaluation of the non-stick potential of lavender oil against Escherichia coli strain (Research, Society and Development, 2021)
Conventional endodontic therapies use mechanical instruments and irrigation solutions to promote canal decontamination; however, the presence of more resistant bacteria and greater capacity to adhere to the dental walls ends up leading to the development of secondary infections. Currently, great advances in scientific research using natural products occur, since extracts and oils from different plants have antimicrobial properties and affect biofilm. The present work evaluated the non-stick potential of Lavandula hybrida Grosso essential oil against Escherichia coli strain. For this, the following were carried out: the evaluation of the Minimum Inhibitory Concentration of Adhesion (MICA) of the oil against E. coli strain and the comparison of the oil's non-stick potency with 0.12% chlorhexidine. The tests were performed using the inclined tube technique to determine the MICA on the glass, in the presence of 5% sucrose. It was observed that the oil showed a 1:16 MICA, while the positive control (0.12% chlorhexidine digluconate) presented a 1: 8 MICA. It is noted that a twice lower oil concentration is necessary to inhibit the adhesion of the bacteria to the tube wall compared to the main chemical antiseptic used in dental treatments. It is concluded that the oil in question is suitable for the development of irrigation solutions of the root canals or to be used as an auxiliary irrigation substance, as it has the ability to inhibit the adhesion of Escherichia coli, one of the bacteria that makes up the pathogenic biofilm found in secondary endodontic infections.